MEMBANGUN KOTA RAMAH ANAK DENGAN BUDAYA KOTA BERSERAMBI BACA - Susi Ratna Sari (Sosial Budaya, 2015)
Town is a public space that has a routine economic activities with a variety of style and dimensions. However, the city also has a social problem is so complex, among the social issues were visible from the problems faced by children in the urban areas. This issue of concern for all of us, because of the problems the child if left this nation will experience a quality of human crisis in the future. The occurrence of problem children in urban areas, such as caused by the lack of facilities and institutions that empower and trial them. For it, one of which urged to designed in town is a recessed porch read accessible and accommodating children in urban areas with its main activity is reading. Therefore, the city of the future will need to cultivate the porch-porch read these, because of the existence of the porch-porch read this children is estimated to be able to change the tradition of patologisnya to the Sepik tradition in building its future.